Effects of various treatments for preventing oral mucositis in cancer patients: A network meta-analysis. - Tzu-Rong Peng; Fang-Pei Tsai; Ta-Wei Wu (PLoS ONE)
Background Oral mucositis (OM) is a common side effect of chemotherapy and radiotherapy in patients with cancers. The prevention or treatment of OM in cancer patients is crucial in the treatment of cancer. Methods We searched PubMed, Embase, and Cochrane Library for the randomized control trials (RCTs) of interventions for preventing and treating OM. Network meta-analysis (NMA) was performed to estimate odds ratios (ORs) and 95% confidence intervals (CI) from both direct and indirect evidence. The prespecified primary efficacy outcome was the treatment effect of moderate to severe oral mucositis with 12 interventions. The outcome was moderate to a severe grade of OM. Results This study included 55 RCTs with 3,552 participants. The results showed that honey significantly lowered the risk of chemo/radiotherapy-induced moderate to severe oral mucositis than placebo (OR: 0.01, 95%CI 0.00 to 0.45), followed by lignocaine (OR: 0.07, 95%CI 0.00 to 0.95). The surface under cumulative ranking curve (SUCRA) values for honey were 0.95, followed by lignocaine (SUCRA, 0.81) and benzydamine (SUCRA, 0.78). Conclusions The honey is effective for patients with cancer undergoing chemotherapy or radiotherapy-induced oral mucositis.